TanDEM-X: A TerraSAR-X Add-On Satellite for Single-Pass SAR Interferometry - Moreira, Alberto; Krieger, Gerhard; Hajnsek, Irena; Hounam, David; Werner, Marian; Riegger, Sebastian; Settelmeyer, Eckard (IEEE Geoscience and Remote Sensing Symposium, 2004)
TanDEM-X is a mission proposal for a TerraSAR-X add-on satellite for high-resolution single-pass SAR interferometry. This mission proposal has been selected for a Phase A study within the scope of a Call for Proposals for a next German Earth Observation Mission to be launched in 2008/2009. The mission has the goal of generating a global Digital Elevation Model (DEM) with an accuracy corresponding to the DTED-3 specifications (12 m posting, 2 m relative height accuracy for flat terrain). This goal will be achieved by means of a second, TerraSAR-X like satellite (TanDEM-X) flying in a close orbit configuration with TerraSAR-X. This paper describes the mission concept and requirements, including several innovative aspects like operation modes, orbit selection and maintenance as well as PRF and phase synchronization. Results from a detailed performance estimation show the achievable DEM accuracy. Finally, an overview of the potential of the TanDEM-X mission for several scientific applications is presented.
DLR Import::2019-04-03
Keywords: Bi-static Radar; Digital Elevation Model (DEM); Interferometry; Mining Target Indication (MTI); Synthetic Aperture Radar (SAR)